Psychological Capital of Generation Z in Facing The Workforce: A Narrative Literature Review - Nu'ma, Farah Almira; Mangunsong, Frieda Maryam (KONSELOR, 2024)
Characteristics of Generation Z (Gen Z), especially final-year university students, have different attitudes, expectations, strengths, and weakness compared to previous generations when facing the job market. However, there is still a lack of literature discussing Gen Z in their career journey. Previous research indicates that psychological capital is a psychological resource by individuals in job performance and adapting to the workforce. This narrative review aims to provide an overview of Psychological Capital (PsyCap) in Gen Z when facing the job market. A literature review was conducted on 24 articles obtained from seven sources: Emerald Insight, Google Scholar, ProQuest, Sage Journal, SpringerLink, Taylor Francis, Science direct and Sinta Database. From the 24 literatures that met the inclusion criteria, this study focuses on four aspects: (1) characteristics Gen Z facing the workforce, (2) the differences PsyCap Gen Z with previous generation, (3) importance PsyCap in facing workforce, (4) and intervention to enhance PsyCap. From the literature analysis, it can be concluded that the PsyCap of Gen Z in several studies shows varied results. Some indicate that Gen Z’s PsyCap in lower than previous generations, while other studies find that Gen Z’s PsyCap is in the medium to high category. These differences show that although there are concerns about the low PsyCap of Gen Z, there is potential that this generation has an openness to possessing good psychological capacities in facing challenges. Therefore, interventions to enhance PsyCap for students are crucial for higher educations institutions to prepare graduates who are psychologically ready to compete in the job market.